2002
DOI: 10.1016/s0361-090x(02)00013-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer screening: stages of adoption among Cambodian American women

Abstract: Background-Little information is available on the breast cancer screening behavior of Cambodian American women.Methods-We identified households from multiple sources using Cambodian surnames and conducted a cross-sectional survey, administered by bilingual and bicultural interviewers. Breast cancer screening stages of adoption were examined based on concepts from the transtheoretical model of behavioral change.Results-Our response rate was 73% (398 women in clinical breast exam (CBE) analysis, and 248 in mammo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 43 publications
(50 reference statements)
2
32
1
Order By: Relevance
“…In contrast, Asian immigrants were the least likely to report recent or ever screening for cervical or breast cancer. This result supports findings of previous studies 30,33,39,[60][61][62] and highlights the need for culturally sensitive interventions targeting this relevant and numerous group. Our study has several limitations.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, Asian immigrants were the least likely to report recent or ever screening for cervical or breast cancer. This result supports findings of previous studies 30,33,39,[60][61][62] and highlights the need for culturally sensitive interventions targeting this relevant and numerous group. Our study has several limitations.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, it has been postulated that the low cancer screening rates among Asian Americans are partly due to the lack of a preventive orientation among providers trained in Asia. 65,66 The small sample size of this study also limited the precision of some estimates (Table 2). Specifically, whereas our results showed that patients with no insurance and patients with private insurance were less likely to complete FOBT testing than were patients on public insurance, due to our small sample size there were no statistically significant differences.…”
Section: Discussionmentioning
confidence: 90%
“…37 Our previous study in Cambodian-American women identified significant associations of physician gender and ethnicity with mammography screening. 12 Because language plays an integral role in the patientphysician encounter, we also examined the association of language concordance with screening behavior in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In the Pathways to Early Cancer Detection Project, compared with white women (93%), black women (91%), and Hispanic women (80%), significantly lower proportions of Chinese women (73%) and Vietnamese women (46%) reported prior mammography screening. 27 It is projected that, by the year 2050, Asians and Pacific Islanders will comprise 10% of the U.S. population.…”
mentioning
confidence: 99%